2018
DOI: 10.1007/s00259-018-4059-3
|View full text |Cite
|
Sign up to set email alerts
|

Developing and validating a novel metabolic tumor volume risk stratification system for supplementing non-small cell lung cancer staging

Abstract: This study developed and validated a novel MTVwb risk stratification system, which has prognostic value independent of the TNM stage and other clinical prognostic factors in NSCLC, suggesting that it could be used for further NSCLC pretreatment assessment and for refining treatment decisions in individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…However, the predictive power of combining the 18 F-FDG PET parameters from both primary tumor and metastatic nodes has not been well investigated. Although some studies have combined the 18 F-FDG PET volumetric parameters from the primary tumor and metastatic lesions, these study cohorts mixed locoregional disease cases with distant metastatic cases [35][36][37][38]. Thus, the results of these studies cannot be applied to patients with locoregional disease due to the diverse prognoses of patients with M0 or M1 diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the predictive power of combining the 18 F-FDG PET parameters from both primary tumor and metastatic nodes has not been well investigated. Although some studies have combined the 18 F-FDG PET volumetric parameters from the primary tumor and metastatic lesions, these study cohorts mixed locoregional disease cases with distant metastatic cases [35][36][37][38]. Thus, the results of these studies cannot be applied to patients with locoregional disease due to the diverse prognoses of patients with M0 or M1 diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical and pathological characteristics have been considered as prognostic factors for survival outcomes. Recently multiple published studies have demonstrated that pretreatment tumor burden measured by PET/CT scan was highly correlated with treatment outcomes in LANSCLC patients receiving definitive CCRT [21][22][23]. Bradley et al [18] concluded that GTV determined by three-dimensional conformal radiotherapy (3DCRT) planning had great prognostic value for long-term survival and local control.…”
Section: Discussionmentioning
confidence: 99%
“…Although incorporating genetic or molecular information could perfectly improve the predictive value of this nomogram and provide more insights into this topic, our nomogram incorporates several valuable clinically available variables and is cheaper than molecular tests, making it a more economical and practical option for survival prediction. PET characteristics of these tumors, such as baseline metabolic tumor volume are innovative and valuable prognostic factors for NSCLC (37)(38)(39). Incorporating these characteristics would definitely make the nomogram more precise and meaningful.…”
Section: Discussionmentioning
confidence: 99%